Treatment of panfacial fracture: sequence of treatment from bottom to up inside out: Case report (Research, Society and Development, 2023)
Panfacial fractures are the most complex and destructive traumatic affections of the facial skeleton, involving the upper, middle and lower thirds. They are usually associated with severe soft tissue injuries and lead to important aesthetic-functional deformities with disruption of facial physiognomy, ophthalmological and dental occlusion alterations. The sequences "bottom-up and inside-out" or "top-down and outside-in" are used to describe two classic approaches to the management of panfacial fractures.1,3 This work aims to report a case of treatment for a panfacial fracture resulting from a motorcycle accident that occurred with a 26-year-old male patient who underwent surgical approaches for the correction of multiple facial fractures, as well as performed and the outcome of the case.